The influence of PJBL Models and Learning Styles on Learning Outcomes - Atiqoh, Atiqoh; Gunawan, Wawan; Ridwan, Agus (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this research is to analyze the differences between the PjBL and Direct instruction models and learning styles on fashion design learning outcomes. This quantitative research uses experimental methods. Researchers used SPSS 25 to calculate a two-way analysis of variance test. The research design used is a 2x3 factorial design. Because this research was conducted in four classes, namely 2 experimental classes and 2 control classes. The experimental class was treated with the PjBL Model while the control class was given the Direct Instruction learning method. Each control class and experimental class were divided into three groups, namely audio, visual and kinaesthetic groups. The data analysis technique in this research is two-way analysis of variance with a significance level of α = 5%. Based on the results of data analysis, there is a significant influence between the PjBL Model and learning styles on Sewing Learning Outcomes. Based on the research results, it was concluded that the use of the PjBL Model and Learning Styles can improve Fashion Design Learning Outcomes.